Macrozoobenthos community structure in Mangrove Ecosystem in Way Kambas National Park Buffer Area - herman yulianto (Akuatik: Jurnal Sumberdaya Perairan, 2023)
Way Kambas National Park is one of the National Parks located in Lampung Province. This area has several types of wetland ecosystems, namely rivers, swamps, and mangroves. The condition of diverse mangrove ecosystems can affect the density and diversity of biota, one of which is macrozoobenthos that live in the region. The purpose of this study is to find out the relationship between mangroves and macrozoobenthos. The study was conducted in January 2021 at Mangrove Way Kambas National Park. Sampling was conducted at 6 stations with different mangrove density conditions, that was, sparse densities at stations I and station 4, as well as solid at stations 2, 3, 5, and 6. In addition to total organic matter, other environmental parameters were also observed including pH, salinity, temperature, dissolved oxygen, substrate type, brightness, and depth. Macrozoobenthos were found to be 12 species of macrozoobenthos namely Polymesoda expansa, Acetes indicus, Illyoplax pacifica, Asiminea brevicula, Terebralia palustris, Clithon oualeniense, Terebralia sulcata, Cerithidea quadrata, Pomacea canaliculata, Telescopium telescopium, Episesarma versicolor, and Planaria torva in 6 research stations. As for the positive correlates with macrozoobenthos density, were pH, salinity, and total organic matter (TOM).